Discovery, Evidence, Confidentiality, and Security Problems Associated with the Use of Computer-Based Litigation Support Systems - Haley J. Fromholz (Washington University Law Quarterly, 1977)
This Article focuses on the problems of admissibility of computerized records in general, and the specific admissibility, confidentiality, and security problems which relate to computerized litigation support systems. Haley J. Fromholz discusses the modifications in the Federal Rules of Evidence and Civil Procedure that provide courts with sufficient discretion to adapt to problems presented by computerization. After reviewing the reported cases, he notes approvingly that courts generally recognize that the presence of computers does not alter the basic rules of evidence, discovery, or confidentiality. He urges lawyers to inform themselves about computers to enable them to recognize when computers can profitably aid in litigation and when they present unique evidentiary or discovery problems requiring new solutions.
Keywords: Discovery; Admissibility of evidence; Federal Rules of Civil Procedure; Urban transportation – Federal aid